تأثير المركب Chitosan في تحفيز مقاومة غراس الزيتون للإصابة بمرض عين الطاووس المتسبب عن الفطر Spilocaea oleagina تحت ظروف العدوى الاصطناعية - طويل محمد; المغربي صباح (Latakia University Journal -Biological Sciences Series, 2018)
To study the effect of Chitosan in stimulating the resistance of olive plants to the infection of eye peacock caused by the fungus Spilocaea oleagina. Olive plants were treated with Chitosan concentration of 300 mg / l. artificial infection was conducted using the fungs spores at different periods on Khadairy variety (susceptible). The infection was done after 2 or 4 weeks of treatment for one time by Chitosan , and two times with a 15 days interval. Copper fungicides (Oxychloro-copper) was used preventively for each treatment. Effectiveness was calculated after 165 days of infection, it was 75.4% and 81.7%, respectively for treatment with Chitosan and infection after 2 or 4 weeks compared with 85.8% and 82.7% for the copper compound. Effectiveness was higher when Chitosan was used for two times (86.9%) compared with the copper compound (88.6%). The total phenol content and the activity of the peroxidase enzyme in the treated plant were assessed after 3 to 6 months of treatment with Chitosan. The total phenol content and peroxidase enzyme activity was increased compard with the control,whereas the highest value was for two treatments with Chitosan. لدراسة تأثير المركب Chitosan في تحفيز مقاومة غراس الزيتون للإصابة بمرض عين الطاووس المتسبب عن الفطر .Spilocaea oleagina تمت المعاملة ب Chitosan بتركيز 300 مغ/ل وتنفيذ العدوى الاصطناعية على فترات مختلفة وذلك على غراس زيتون من الصنف خضيري المعروف بحساسيته للإصابة بالمرض. أجريت العدوى بعد 2 أو4 أسابيع من المعاملة لمرة واحدة بالمركب، أو معاملتين بفارق 15 يوم. كما استخدم مبيد معتمد من مركبات النحاس (أوكسي كلورو النحاس) بشكل وقائي لكل معاملة. حسبت الفاعلية بعد 165 يوم من العدوى وكانت 75.4 و81.7% على التوالي للمعاملة بالمركب والعدوى بعد 2 أو 4 أسابيع مقارنة مع 85.8 و82.7 % للمركب النحاسي، وكانت أعلى فاعلية عند إجراء معاملتين ب Chitosan حيث وصلت إلى 86.9% مقارنة مع 88.6% للمركب النحاسي. تم دراسة تغيرات المحتوى الكلي للفينول ونشاط أنزيم البيروكسيداز في الغراس المعاملة وذلك بعد 3 و6 أشهر من المعاملة ب Chitosan ولوحظ زيادة المحتوى الكلي للفينول ونشاط أنزيم البيروكسيداز يالمقارنة مع الشاهد وكانت أعلى قيم لهما عند المعاملة مرتين بالمركب Chitosan.